2015
DOI: 10.17582/journal.sja/2015/31.3.165.174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Allelopathic Water Extract of Sorghum and Sunflower on Weed Mortality and Cotton Yield

Abstract: Sorghum and sunflower have been reported to contain several allelochemicals. Utilization of these allelochemicals is considered low-cost and natural sources for weed suppression. Field trials were undertaken at Cotton Section, Agriculture Research Institute, Tandojam Pakistan during summer 2010 and repeated during summer 2011 for validating the previous results. The experiments were laid out in three replicated randomized complete block design. The seed of cotton variety "Sindh-1" was sown through drilling in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
2
7
0
1
Order By: Relevance
“…The treatments with sunflower residues showed the highest suppression of weeds as compared to treatments with sunflower water extracts (Table 4). Kandhro et al (2015) and Farooq et al (2011) reported a significant reduction in weed density (25.26%) and dry weight (14.60%) resulting from the application of sunflower water extract. The highest suppression of weeds was recorded in the wheat field as a result of sunflower residue incorporation because of the release of allelochemicals as well as the reduction of light penetration (Reberg-Horton et al, 2005;Alsaadawi et al, 2007).…”
Section: Yield Componentsmentioning
confidence: 99%
“…The treatments with sunflower residues showed the highest suppression of weeds as compared to treatments with sunflower water extracts (Table 4). Kandhro et al (2015) and Farooq et al (2011) reported a significant reduction in weed density (25.26%) and dry weight (14.60%) resulting from the application of sunflower water extract. The highest suppression of weeds was recorded in the wheat field as a result of sunflower residue incorporation because of the release of allelochemicals as well as the reduction of light penetration (Reberg-Horton et al, 2005;Alsaadawi et al, 2007).…”
Section: Yield Componentsmentioning
confidence: 99%
“…The allelopathic weeds contain compounds with phytotoxic ability in their aerial and underground parts like leaves, flowers, seeds, stems and roots in varying concentrations (Tesio & Ferrero, 2010). In a study by Kandhro et al, (2015) in Pakistan, sorghum and sunflower were found to have high allelopathic potential, containing several allelochemicals such as sorgoleone, glycosides, terpenoids, flavonoids, alkaloids and phenolics. Farooq et al, (2013) also found out that allelopathic compounds secreted by sunflower suppressed the germination and growth by interruption of metabolic activities of wheat plant cells.…”
Section: Research Articlementioning
confidence: 99%
“…Naeem et al, (2018) revealed that weeds reduce the quality of the crop produce and yields, as well as increase the costs of production and harvesting. Severe weed infestations in crop fields due to abundance of weed seeds in the soil greatly affects crop yields in smallholder farming systems (Kandhro et al, 2015). In Zimbabwe, weeds continue to persist in many agro-ecological regions having a wide and large weed seed bank (Chachar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of secondary metabolites / allelomones produced by some of the plants act as potential natural herbicides with considerable crop selectivity, which could be directly used in the form of aqueous plant water extracts for weed management in organic and sustainable agriculture systems. The application of allelopathic aqueous extract of sorghum 25 L ha -1 twice at 15 and 30 DAS resulted in reduced weed density as compared to all other plant aqueous extract treatments in cotton grown in clay loam soils of Peshwar, Pakistan (Kandhro et al ., 2015). In this context, there is a need to evaluate the performance of different plant aqueous extracts for weed management in groundnut and their effect in soil microorganisms in sandy loam soils.…”
Section: Introductionmentioning
confidence: 99%